KAJIAN PENYESUAIAN GOLONGAN DAN TARIF TOL DENGAN MEMPERTIMBANGKAN PENGRUSAKAN PERKERASAN JALAN OLEH KENDARAAN BERAT - Hikmat Iskandar (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
The increase of toll tariff became a hot issue among toll road operators and users. Although it was not popular among toll road users, the toll road operators expected to increase their income. According to Toll Regulation no. 15, 2006, the change in toll tariff is applied every two years in accordance with inflation. In the mean time toll operators expected the increase of toll tariff due to the increase of pavement damage caused by the increase of vehicle load which in turn would increase the maintenance cost. This paper discusses the analysis of toll tariff changes in relation with existing vehicle axle loads and its application by considering the above regulation. The results indicated that 1) considering distribution and magnitude of axle loads of each type of vehicles, it is reasonable to reclassify vehicle types to be more classes e.g. from 3 to 7 and 2) The increase of toll tariff on operated toll roads due to pavement damage caused by excessive vehicle axle loads has no legal basic, except if it is inclusive in the whole calculation of toll road business plan. Keywords : Toll Tariff, Vehicle Load